Method of Integrated Assessment of the Effectiveness of Regional Labour Market Infrastructure - Nurali Uralovich, Arabov; Dilmurod Abdulloevich, Nasimov; Burkhon Sadinovich, Boltayev; Alisher Batirovich, Mirzakhodjaev (International Journal of Psychosocial Rehabilitation, 2020)
The research is dedicated to the development of the integrated assessment method using specific indicators that characterize the effectiveness of the development of components of the regional labor market infrastructure and scientifically and practically substantiates the possibility of assessing the dynamic efficiency of infrastructure development and determining the share of changes in its particular components.